SYSTEMATIC LITERATURE REVIEW: ANALISIS BAHAN AJAR BERBASIS ETNOMATEMATIKA DAN EVOLUSI BAHAN AJAR BERBASIS LANSKAP LINGUISTIKA MATEMATIS - Mukmilah, Amaliyah; Rayungsari, Maya (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2024)
The role of teaching materials in the learning process is crucial, as they are served as the primary resources supporting students' learning endeavors. One of the various teaching materials have been developed, is ethnomathematics-based material, the latter often come with cultural limitations. Therefore, the purpose of this research is to identify teaching materials suitable for learning processes without cultural constraints. The Systematic Literature Review (SLR) method was employed for this study. Data collection involved gathering national and internationally indexed articles published within the last five years. Seventeen articles matching the keywords were selected from Google Scholar. The research findings indicate a requirement for teaching materials grounded in mathematical linguistic landscapes that transcend cultural boundaries. Consequently, there is a necessity to develop teaching materials, such as e-modules and worksheets (LKPD), grounded in mathematical linguistic landscapes to ensure inclusivity and accessibility for all students, regardless of cultural backgrounds.